Food Allergy and the Microbiome: Current Understandings and Future Directions - Bunyavanich, Supinda (J Allergy Clin Immunol, 2019)
Growing evidence points to an important role for commensal microbiota in susceptibility to food allergy. Epidemiologic studies demonstrate associations between exposures known to modify the microbiome and risk of food allergy. Direct profiling of the gut microbiome in human cohort studies has demonstrated that individuals with food allergy have distinct gut microbiomes compared to healthy controls, and dysbiosis precedes the development of food allergy. Mechanistic studies in mouse models of food allergy have confirmed that the composition of the intestinal microbiota can imprint susceptibility or resistance to food allergy on the host, and have identified a unique population of microbial-responsive RORγt+ Foxp3+ Tregs as critical for the maintenance of tolerance to foods. Armed with this new understanding of the role of the microbiota in food allergy and tolerance, therapeutics aimed at modifying the gastrointestinal microbiota are in development. In this manuscript, we review key milestones in the development of our current understanding of how the gastrointestinal microbiota contributes to food allergy and discuss our vision for the future of the field.